Contemporary Views on Community Resilience: Lessons for Preparing Social Workers - Stoliaryk, Olha (Social work and education, 2025)
This article examines the integration of community resilience factors into the training system for social workers through a systemic approach encompassing adaptive relationships, learning, and development within socio-ecological systems. It explores the necessity of updating educational programs, mainly through interdisciplinarity, the development of practical skills, and the formation of competencies for effective crisis response.​ Based on literature analysis, the article defines community resilience through four key elements: community resources, the ability to adapt, absorb crisis impacts, and recover. It discusses the influences of social capital, leadership, institutional interaction, and economic diversification. Specifically, it analyzes factors identified by scholars that contribute to community resilience, such as self-organization, adaptive mechanisms, infrastructure development, and risk management.​ Special attention is given to the development and substantiation of a list of key competencies for social workers necessary to ensure community resilience. The importance of including components in social work educational programs that promote the development of skills and abilities to assess local resources, implement crisis management, and foster social cohesion within the local territorial community is emphasised. The article underscores the role of social workers in enhancing community safety and well-being through the development of economic capacity, resource management, and support for the local population.​ The conclusions highlight the need to adapt educational programs to contemporary challenges, particularly through the integration of modules on crisis response, community leadership, and strategic planning.